The discard of deceased donor kidneys in the UK. (8th February 2014) - Callaghan, Chris J.; Harper, Simon J.F.; Saeb‐Parsy, Kourosh; Hudson, Alex; Gibbs, Paul; Watson, Christopher J.E.; Praseedom, Raaj K.; Butler, Andrew J.; Pettigrew, Gavin J.; Bradley, J. Andrew
Abstract It is essential to minimize the unnecessary discard of procured deceased donor kidneys, but information on discard rates and the extent to which discard can be avoided are limited. Analysis of the UK Transplant Registry revealed that the discard rate of procured deceased donor kidneys has increased from 5% in 2002‐3 to 12% in 2011‐12. A national offering system for hard‐to‐place kidneys was introduced in the UK in 2006 (the Declined Kidney Scheme), but just 13% of kidneys that were subsequently discarded until 2012 were offered through the scheme. In order to examine the appropriateness of discard, 20 consecutive discarded kidneys from 13 deceased donors were assessed to determine if surgeons agreed with the decision that they were not implantable. Donors had a median (range) age of 67 (31–80) yr. Kidneys had been offered to a median of 3 (1–12) centers before discard. Four (20%) of the discarded kidneys were thought to be usable, and nine (45%) were possibly usable. As a result of these findings, major changes to the UK deceased donor kidney offering system have been implemented, including simultaneous offering and broader entry criteria for hard‐to‐place kidneys. Organizational changes are necessary to improve utilization of deceased donor kidneys.